Practicing and factors infuencing the effective implementation of Strategic Information Systems Planning in public agency - Sukhaila Angsor; Maryati Mohd Yusof (Penerbit Universiti Kebangsaan Malaysia, 2019)
Strategic Information Systems Planning (SISP) guided organization in achieving its target. The importance of SISP increases proportionately with the uncertainty of business requirements. Failures in implementing SISP may affect organizational service delivery and reputation. This paper discusses on the evaluation of the practice and influencing factors of SISP implementation in a public sector. The Human Organization Technology-fit framework was used to evaluate the effectiveness of SISP from human, organization and technology perspectives. A qualitative case study was conducted using interview and document analysis method. The study identified 25 influencing factors of SISP implementation including knowledge and expertise, stakeholder engagement; governance, top management support, financial allocation and infrastructure capabilities. These influencing factors can guide other agencies to identify the risks of SISP implementation at an early stage; subsequently, mitigation plan can be developed to minimize the risk.